Latinos in the Midwest - Martinez, Ruben Orlando (Latinos in the United States series., 2011)
Over the past twenty years, the Latino population in the Midwest has grown rapidly, both in urban and rural areas. As elsewhere in the country, shifting demographics in the region have given rise to controversy and mixed reception. Where some communities have greeted Latinos openly, others have been more guarded. Despite their increasing presence, Latinos remain the most marginalized major population group in the country. In coming years, the projected growth of this population will require greater attention from policymakers concerned with helping to incorporate them into the nation's core institutions. This eye-opening collection of essays examines the many ways in which an increase in the Latino population has impacted the Midwest--culturally, economically, educationally, and politically. Drawing on studies, personal histories, legal rulings, and other sources, this book takes an interdisciplinary approach to an increasingly important topic in American society and offers a glimpse into the nation's demographic future.--Publisher description.